الاختلاس الإلكتروني للمال العام في التشريع الإماراتي دراسة تحليلية - عارف عبد الله محمد الوادعي
In view of the acceleration of countries in developing electronic systems and achieving a positive impact in facilitating the burden on societies regarding government services and others, they are however naturally not free from the problem of misuse, such as committing various crimes. This includes the crime of Peculation of public funds through electronic means. The problem of the study lies in the fact that the Law on Countering Rumors and Cybercrimes and its amendments did not establish the crime of Peculation of public funds through electronic tools and systems, and the relevant provisions such as the crime of forgery, explicitly. The study aims to identify the crime of electronic Peculation of public funds and the position of the UAE Legislation in countering and limiting its spread. It also aims to clarify the penalties and penal provisions established by the UAE Legislator and their proportionality, and to elucidate the judge's authority in assessing the penalty that was not established in the law. The researcher applies two methods to clarify this: the inductive and analytical methods to texts, opinions, judicial judgments, and related issues. The importance of this research is to consider the gaps and loopholes found in the law provisions related to countering the crime of electronic Peculation. This is to avoid exploitation by the criminals in evading the laws and regulations established by the UAE Legislator in particular, as well as resisting and countering the crime of electronic Peculation of public funds. One of the most important findings is that the scholars are not in agreement on the concept of Peculation, whether in law or Sharia. However, contemporary legal scholars have distinguished themselves in stating the basic elements of the crime of Peculation. The study establishes several recommendations, including detailed descriptions of crime of electronic Peculation of public funds through electronic tools and systems that are still ambiguous, as well the stipulation provisions in the Law on Countering Rumors and Cybercrimes which are similar to the crime of forgery and fraud. In analyzing the crime of electronic Peculation of public funds, the related provisions, and issues, and also the position of the UAE Legislator in countering crime through the procedures and measures that were taken, it is concluded that amendments are required by stipulating the punishment explicitly for everyone who commits such crimes. This is to ensure that there is no possible way to evade the justice and tampering with the public funds.